Screening for Dysglycemia: Connecting Supply and Demand to Slow Growth in Diabetes Incidence. - Mohammed K Ali; K M Venkat Narayan (PLoS Medicine)
Mohammed Ali and Venkat Narayan describe the challenge of implementing evidence-based interventions for prevention for the large number of people at increased risk of type 2 diabetes.